Vectored introductions of marine endosymbiotic dinoflagellates into Hawaii - Stat, Michael; Gates, R. (Springer, 2008)
Endosymbiotic dinoflagellates belonging to the genus Symbiodinium associate with a diverse range of marine invertebrate hosts and also exist free-living in the ocean. The genus is divided into eight lineages (clades A-H), which contain multiple subclade types that show geographic and host specificity. It is commonly known that free-living dinoflagellates can and have been introduced to new geographic locations, primarily through shipping ballast water. In this study we sequenced the ITS2 region of Symbiodinium found in symbiosis with the coral Acropora cytherea in the Northwestern Hawaiian Islands Marine National Monument and from shipping ballast water. Identification of an unusual symbiont in Acropora cytherea and an analysis of the distribution of this symbiont suggests an introduction to Hawaii vectored by the scyphozoan host, Cassiopea sp. Symbiodinium were also detected in shipping ballast water. This work confirms that marine invertebrate endosymbionts can be introduced to new geographic locations vectored by animal hosts or the ballast water of ships. © 2007 Springer Science+Business Media B.V.